2021
DOI: 10.1002/nau.24682
|View full text |Cite
|
Sign up to set email alerts
|

Is coronavirus disease 2019 associated with indicators of long‐term bladder dysfunction?

Abstract: Objective Early reports have suggested that coronavirus disease 2019 (COVID‐19) can present with significant urinary frequency and nocturia, and that these symptoms correlate with markers of inflammation in the urine. We evaluated surrogate markers of chronic urinary symptoms to determine if they were more frequent after COVID‐19 infection. Methods Routinely collected data from the province of Ontario was used to conduct a matched, retrospective cohort study. We identified patients 66 years of age or older who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In the acute phase, increased urinary frequency has been previously reported in 1/8 of male patients, and suggested to be secondary to viral cystitis due to underlying COVID-19 disease [66]. However, despite these potential mechanisms, a large cohort study found bladder dysfunction not significantly increased in the 2-5 months after COVID-19 infection [67]. In our sample, 1/4 to 1/2 of the sample reported some sort of urinary dysfunction, including both involuntary voids and voiding difficulty.…”
Section: Discussionmentioning
confidence: 95%
“…In the acute phase, increased urinary frequency has been previously reported in 1/8 of male patients, and suggested to be secondary to viral cystitis due to underlying COVID-19 disease [66]. However, despite these potential mechanisms, a large cohort study found bladder dysfunction not significantly increased in the 2-5 months after COVID-19 infection [67]. In our sample, 1/4 to 1/2 of the sample reported some sort of urinary dysfunction, including both involuntary voids and voiding difficulty.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study conducted with a large patient population over 66 years of age has found no significant increase in the development of urinary storage symptoms, medication due to overactive bladder, or the need for urological intervention during the first 5 months after diagnosis of COVID‐19. 14 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted with a large patient population over 66 years of age has found no significant increase in the development of urinary storage symptoms, medication due to overactive bladder, or the need for urological intervention during the first 5 months after diagnosis of COVID-19. 14 LUTS developing on the background of depression, anxiety, or other stress symptoms (insomnia, etc.) without a neurologic or organic etiology has been defined as bladder somatic symptom disorder.…”
Section: Discussionmentioning
confidence: 99%
“…BPH and radiation cystitis); the authors hypothesize that the previous urological conditions made the patients especially vulnerable to damage to the urinary tract by COVID-19, including hematuria [ 24 ]. Interestingly, Welk and colleagues have reported that there was no increase in urology consultation, cystoscopy, or overactive bladder medication prescription among patients who had COVID-19, compared to the matched cohort [ 25 ]. However, their study was limited in that it did not contain patient reported outcome measures, or direct measures of urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%